Asthma underdiagnosis in children: A school-based screening in a low socioeconomic status population - Dayan Crispin-Cruz; Alejandro Casas-Herrera; Camilo Rojas-Báez; Carlos Torres-Duque; Mauricio González-García (Biomédica: revista del Instituto Nacional de Salud)
Introduction. International asthma management and prevention recommendations emphasize the importance of early and accurate diagnosis and adequate disease control. However, these aspects remain a serious concern, especially in children with low socioeconomic status. Objective. To describe asthma prevalence, underdiagnosis, severity, and control among children with low socioeconomic status in Bogotá, Colombia. Materials and methods. We conducted a cross-sectional study using the International Study of Asthma and Allergies Questionnaire in children aged 7-11 in two public schools. The children with affirmative answers in the questionnaire were evaluated clinically and functionally at the mobile health care unit. Asthma prevalence, underdiagnosis, control level, severity, and patients’ quality of life were assessed with validated instruments. Results. We screened 920 schoolchildren with an age of 9.5 ± 1.1; 186 were evaluated clinically and functionally by spirometry, and 122 of them were diagnosed with asthma (17.2%). Underdiagnosis was 68%. Most patients had moderate and severe asthma, and 90% were cases of not well or very poorly controlled asthma. Conclusions. Screening children in school settings is a suitable strategy for detecting asthma and reducing underdiagnosis in communities with low socioeconomic status and limited access to health care services. The asthma underdiagnosis and poor disease control were high.